Farm Women Livelihood in Maize Production and Utilization in Bihar - Usha Singh, Shilpi (Indian Journal of Extension Education, 2022)
In Indian, agriculture is the main base of the national economy. It engages 64 per cent of its population and contributes to 26.1 per cent of the nationa income according to 2001-2002 a report. Agricultre employes both men and women participation in agriculture to grow, cultivate and manage farms to fulfill the basic need of food for human beings. The importance of women’s participation in agriculture has been reported by the investigators (Bhatt, 1988; Lal, 1988; Anandlakshmy and Swaney, 1988) They are engaged both as cultivators and as agricultural labours, irrespective of their age, family size, landholding, caste and community. The extent of participation of woman is governed by environmental factors, personal attributes, knowledge and skills as well as family control.